Green building illustrated - Ching, Francis D.K.; Shapiro, Ian M. (Hoboken, New Jersey : John Wiley & Son, Inc., 2021)
This guide explains why we need to build green, the theories behind green building, and advancements in the industry--with a focus on sustainable sites, approaching net-zero energy, low water usage, minimum-impact materials and superior indoor environmental quality. Updates to this edition include: all-new case studies featuring buildings with proven zero energy performance; expanded guidance for the schematic design of high-performance buildings; strategies for affordability in green design and construction; and expanded coverage of complex green building topics, such as heating system and hot water selection, building envelopes, and integrating renewable energy.
Preface vii -- 1 Introduction 1 -- 2 First Principles 13 -- 3 Codes and Standards 27 -- 4 Community, Climate, and Site 43 -- 5 Building Shape and Biomimicry 69 -- 6 Near-Building Features 89 -- 7 Outer Envelope 101 -- 8 Unconditioned Spaces 133 -- 9 Inner Envelope 147 -- 10 Thermal Zoning and Compartmentalization 159 -- 11 Lighting, Plug, and Process Loads 169 -- 12 Hot and Cold Water 185 -- 13 Indoor Environmental Quality 197 -- 14 Heating and Cooling 217 -- 15 Renewable Energy 237 -- 16 Net-Zero Energy Design and Case Studies 245 -- 17 Materials 253 -- 18 Schedules, Sequences, and Affordability 271 -- 19 Quality in Green Design and Construction 281 -- 20 Conclusion 303 -- Glossary 309 -- Bibliography 313 -- Index 317.
Includes bibliographical references and index.
Keywords: BUILDING DETAILS